Role of D-dimer Assays in the Diagnostic Evaluation of Pulmonary Embolism. (December 2015) - Jain, Snigdha; Khera, Rohan; Suneja, Manish; Gehlbach, Brian; Kuperman, Ethan
Abstract : Abstract: The diagnosis of pulmonary embolism (PE) remains challenging despite the evolution of well-validated clinical algorithms over the past few decades, largely because of nonspecific clinical features altering clinician suspicion. D-dimer is a simple noninvasive test that is an essential part of the diagnostic algorithm but is often deemed to be of little value in patients who are elderly or have other comorbidities. We describe a case of an elderly man who presented with clinical features and initial imaging consistent with pneumonia and a positive D-dimer test. Adherence to the suggested diagnostic algorithm and obtaining chest imaging, however, prevented what could have been a catastrophic missed diagnosis of PE. We review existing evidence on the importance of suspecting PE in the presence of alternative diagnosis and explore the literature on the association between the magnitude of D-dimer and the diagnosis of PE.